3D reconstruction of complex spatial weld seam for autonomous welding by laser structured light scanning. (March 2019) - Zhang, Ke; Yan, Minzhi; Huang, Tianyu; Zheng, Jian; Li, Zhuguo
Abstract: As to improve the accuracy, efficiency and flexibility of welding process, intelligent welding is an inevitable trend in the future. To realize the modeling of autonomous welding path planning to the spatial complex weld of large workpiece, we designed a weld path autonomous programming system based on laser structure light, which effectively obtained three-dimensional (3D) information of workpiece by multiple segment scanning, then extracted weld features by grayscale image processing, and reconstructed spatial complex curve seam model by cubic smoothing spline and detected characteristic parameters of lap joints, contributing to subsequent self-generated welding procedures. Besides, experimental results showed that the recognition accuracy of the spatial curve seam by proposed method was within 0.4 mm, meeting the weld tracking requirements.